Yield and soil fertility trends in a 20-year rice-rice-wheat experiment in Nepal - Regmi, A.P.; Ladha, J.K.; Pathak, H.; Pasuquin, E.; Bueno, C.; Dawe, D.; Hobbs, P.R.; Joshy, D.; Maskey, S.L.; Pandey, S.P. (Wiley, 2002)
The rice (Oryza sativaL.)–wheat (Triticum aestivumL.) cropping system occupies about 13.5 million ha in South Asia and is important for the region's food security. We examined the long‐term yield trends, changes in soil nutrient fractions (both total and available), and nutrient balances in a 20‐yr rice–rice–wheat experiment conducted in the Indo‐Gangetic plain of Nepal. The yield of first rice crop fertilized with recommended NPK fertilizer or farmyard manure (FYM) declined an average of 0.09 or 0.07 Mg ha−1yr−1, respectively. These 20‐yr trends explained only 20 to 21% of the variability in yield, and inexplicable shorter‐term yield trends were observed. Likewise, wheat yield declined at 0.05 Mg ha−1yr−1(with both NPK and FYM) over the 20 yr. However, the yield of second rice crop did not decline over that period. The total and available N and P, and total and labile C contents of soil from Year 10 to 20 were either maintained or increased, but total K and available K declined. The apparent K balance showed net losses of 62.3 and 15.2 kg K ha−1yr−1with NPK and FYM treatments, respectively. Depletion of soil K and inadequate K fertilization seems to be the primary reasons of limited and declining yield of first rice and wheat crop. In addition, the yield of wheat declined because of a delay in sowing, which was estimated to be 0.04 Mg ha−1for each day delay in sowing. The study showed that the current local fertilizer recommendations, particularly for K, for the rice–rice–wheat system are inadequate.